Synchrotron X-ray Absorption and In Vitro Bioactivity of Magnetic Macro/Mesoporous Bioactive Glasses - Thanida Charoensuk; Wanwisa Limphirat; Chitnarong Sirisathitkul; Witoon Tangwatanakul; Pongsakorn Jantaratana; Upsorn Boonyang (Nanomaterials and Nanotechnology)
Iron oxides in macro/mesoporous bioactive glasses were characterized by synchrotron X-ray absorption near edge structure (XANES) spectroscopy. This magnetic phase was introduced by adding Fe(NO3)3 9H2O during the sol-gel synthesis. The obtained bioactive glass scaffolds exhibited superparamagnetism, in which the magnetization was increased with the increase in the Fe molar ratio from 10 to 20%. The linear combination fits of the XANES spectra indicated that the increase in the Fe molar ratio to 20% enhanced the γ-Fe2O3 formation at the expense of the α- Fe2O3 phase. This variation also promoted the formation of fine-grained bone-like apatites on the surface of the scaffolds in the in vitro test. The apatite growth between three and seven days was confirmed by the changing elemental compositions. However, the highest magnetic proportion led to the distortion of the skeleton walls and the collapse of the porous networks.